LEVEL OF PHYSICAL ACTIVITY AND QUALITY OF LIFE OF UNIVERSITY STUDENTS (Fiep Bulletin - online, 2025)
Introduction: A better quality of life (QoL) is strongly associated with healthy behaviors and the regular and systematic practice of physical activity is a fundamental factor. Despite the intense academic routine, university students in the health area are expected to have a considerable level of physical activity (NAF) and good QoL, due to a better understanding of the benefits for health promotion and maintenance. Objective: To verify the NAF and QoL of university students in the health area at the State University of Piauí (UESPI), comparing courses. Results: The sample consisted of 40 university students of both sexes, enrolled in the Physical Education (n=20) and Nursing (n=20) courses at UESPI-Picos, with an average age of 22.3±4.1 years. Two questionnaires were used: the International Physical Activity Questionnaire (IPAQ short version) to measure NAF and the World Health Organization Quality of Life (WHOQOL Brief) to assess QOL, both in Portuguese, as well as a sociodemographic questionnaire. The data was analyzed using SPSS® version 25.0. Conclusion: Physical education students had significantly higher QoL scores in the physical (p
Keywords: sedentary behavior; students; physical exercise; quality of life